2022
DOI: 10.1021/acs.est.2c02344
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do Emission Factors Approximate Emission Changes from Electricity System Models?

Abstract: Multiple forms of marginal and average emission factors have been developed to estimate the carbon emissions of adding technologies, such as electric vehicles or solar panels, to the electricity grid. Different methods can produce very different results and conclusions, indicating that choosing between methods is not trivial. Researchers would therefore like to know how well these emission factors can approximate emission changes in the actual power grid. This question remains unanswered because of the difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Grid Model Selection. There has been much debate over the correct way to model the electricity grid, 16,28,73,74 and although this study is focused on marginal emission rates, we acknowledge that this debate is not settled in the energy and emissions modeling community. Marginal emission rates have been used by several studies to predict electricity grid emissions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grid Model Selection. There has been much debate over the correct way to model the electricity grid, 16,28,73,74 and although this study is focused on marginal emission rates, we acknowledge that this debate is not settled in the energy and emissions modeling community. Marginal emission rates have been used by several studies to predict electricity grid emissions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There has been much debate over the correct way to model the electricity grid, ,,, and although this study is focused on marginal emission rates, we acknowledge that this debate is not settled in the energy and emissions modeling community. Marginal emission rates have been used by several studies to predict electricity grid emissions. ,, Holland et al argue that a marginal grid model is the correct method for modeling GHG emissions in the United States, pointing to prior studies that show that marginal emission factors more accurately predict electric vehicle emissions over average emission factors. , Gagnon et al argues that short-run marginal emission rates do not consider the fact that large, persistent changes in demand can structurally change the electricity system, impacting emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the AP2 model coupled with marginal emissions used to estimate the marginal damages from power generation accounts for the location in which these emissions from power generation occur, as well as for the fact that the consequent damages occur both close to the power plants and far away (as air pollution is transported). We use 2018 data for MEFs as that is the latest data available and we draw on MEFs with a monthly hour of day resolution given that the precise hour of day estimates do not necessarily deliver higher accuracy . Note that, while the U.S. electricity grid is expected to decarbonize over the next decade, it is not necessary that MEFs will fall.…”
Section: Datamentioning
confidence: 99%
“…We use 2018 data for MEFs as that is the latest data available and we draw on MEFs with a monthly hour of day resolution given that the precise hour of day estimates do not necessarily deliver higher accuracy. 53 Note that, while the U.S. electricity grid is expected to decarbonize over the next decade, it is not necessary that MEFs will fall. For example, recent literature has shown that, even though average emissions have fallen by 28% nationally over the past decade, marginal emissions have increased by about 7%.…”
Section: ■ Datamentioning
confidence: 99%
“…20 ktCO2e) to a 3.5% decrease (1,827 ktCO2e) from January 2015 to November 2021. While yearly marginal emissions factors are a historical simplification of numerous short-term changes to electricity generation determined by dispatch models, recent modeling studies suggest that they perform reasonably well at predicting emissions from demand shifts 56. Changes to hospitalizations associated with PECHospitalization data come from the statistical registry of hospital beds and visits which details morbidity across Ecuador, managed by the National Statistical Agency (INEC).…”
mentioning
confidence: 99%